(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
The article discusses the problems of equivalence of moral and spiritual concepts in the Uzbek translation of the novel by F.M. Dostoevsky "The Brothers Karamazov". The object of this research is the religious and moral concepts that form the philosophical structure of the work, including the categories of faith, freedom, sin, responsibility, suffering, repentance and love. The subject of this research is the ways of conveying these concepts in the Uzbek translated version and the degree of their semantic, functional and pragmatic equivalence in relation to the original text. The methodological basis is the provisions of the theory of translation, the concept of dynamic and functional equivalence, as well as the cognitive-discursive analysis of a literary text. As a result, the features of the transformation of spiritual vocabulary, religious terminology and moral and philosophical concepts in the context of intercultural communication are revealed. It is concluded that equivalence in the Uzbek translation is achieved mainly at the level of functional and semantic correspondence, while preserving the ideological depth of the work, but with the inevitable adaptation of cultural and religious shades.